Hadis tentang Bullying dan Relevansinya terhadap Kesehatan Mental Remaja (Imam Muslim 4650) (IAIN KENDARI, 2023)
Bullying is closely related to a person's mental health. Mental health is a branch of science that studies mental health that focuses on a healthy spirit by looking at human behavior as a complex psychophysical form. Mental health is the formation of compatibility and harmony between one psychological role and another so as to produce a balanced adjustment between humans and the surrounding environment. The result of mental health can be seen from psychological distress, which is a negative impact of bullying. Based on this research, it can be seen that victims of bullying have negative dispositions in themselves including anxiety, antisocial mental distress, and in the long term it has an impact on their future spouses and their children. and in the long term, it has an impact on their future spouse as well as their school life or future career. future career. Not only psychological distress, victims of bullying are generally affected by psychological well-being stating that they feel less happy than people who are not affected by bullying. less happy than people who are not affected by bullying.